2012
DOI: 10.1021/jp307156c
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mechanism-Controlled Ternary Memory Devices Fabricated by Random Copolymers with Pendent Carbazole and Nitro-Azobenzene

Abstract: In the designed copolymers of poly(9-(4-vinyl benzyl)-9H-carbazole) (PVCz)-random-poly(1-(4-nitro-azophenyl)-pyrrole-2, 5-dione) (PMIDO3), carbazole donor and nitro-azobenzene acceptor are introduced into the lateral chains to induce charge transfer under an electric field, and the resulting copolymers have a progressive increase in the nitrogen content to induce filamentary conduction. The fabricated devices with a simple sandwich configuration distinctively exhibit three conductivity states when a negative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
0
33
1
Order By: Relevance
“…And as shown in the DTG curves, the polymers have two main unstable points of 391°C and 446°C because of the degradation of the side chain and the backbone of the polymer respectively, while a tiny weight loss (1%) at a temperature around 150°C was caused by the evaporation of water absorbed on the polymer surface. From all above, the thermal property of CN‐Azo‐PES is comparable with that of polyimides and better than the other polymer materials that have been reported for electrical memory usage . And to the best of our knowledge, in the memory storage processes, the outstanding thermal stabilities will make contributions to the performance of the devices for the absence of thermal decomposition.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…And as shown in the DTG curves, the polymers have two main unstable points of 391°C and 446°C because of the degradation of the side chain and the backbone of the polymer respectively, while a tiny weight loss (1%) at a temperature around 150°C was caused by the evaporation of water absorbed on the polymer surface. From all above, the thermal property of CN‐Azo‐PES is comparable with that of polyimides and better than the other polymer materials that have been reported for electrical memory usage . And to the best of our knowledge, in the memory storage processes, the outstanding thermal stabilities will make contributions to the performance of the devices for the absence of thermal decomposition.…”
Section: Resultsmentioning
confidence: 58%
“…In particular, the high photosensitivity of the azo dye molecules makes azobenzene polymers popular for use as optical and electronic materials. Also according to the literature, some azobenzene derivatives can be induced by an electric field . Kang and his coworkers have demonstrated that polymers bearing pendent azobenzene chromophores with electron‐accepting terminal moieties exhibit write‐once read‐many (WORM) behavior which is attributed to charge trapping at the azobenzene chromophores and that the device has a low onset voltage .…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] These new absorptionp eaks are ascribed to NÀH( nNÀHa t3 666 cm À1 )a nd CÀH( nCÀHa round 2970 cm À1 and 2920 cm À1 )f or all graft polymers. [32][33][34][35] Thus, the presence of DHI or NPH moieties anchored onto the pendant polymers can be confirmed by the changes in the IR spectra line shapes of the polymers.…”
Section: Chemical Composition Analysismentioning
confidence: 85%
“…Furthermore, the rod‐like trans isomer can be used as a mesogenic group for liquid crystals. Focusing on such reversible structural changes and its liquid crystallinity, many applications, such as polymer actuators, holographic optical elements (HOEs), light‐responsive elastomers, and polymer memories, are expected for azobenzenes. However, there are few reports on polymers in which azobenzene units are introduced in the main chain.…”
Section: Introductionmentioning
confidence: 99%